Anamneza in klinični pregled pri odraslem bolniku z infekcijsko boleznijo - Tomažič, Janez (Medicinski razgledi, 2009)
Infectious diseases are beeoming more complicated to diagnose and treat. History plays a eritical role in narrowing the differential diagnosis and deeiding on the most appropriate diagnostie tests. Symptoms of ten are transient and are sometimes reeal1ed by the patient only after repeated inquiry by the doetor. In addition to a eareful history, eareful physieal examination is also very important. History and physical examination of the most importam infeetious disease and syndromes are presented in the article
Keywords: Communicable Diseases; Meningitis; Diagnosis; Anamneza; Medical History Taking; Zdravstveno stanje; Physical Examination; Infekcijske bolezni; Health Status; Fizikalna preiskava; Encefalitis; Encephalitis; Endokarditis; Pneumonia; Pljučnica; Endocarditis; Gastrointestinal Contents; infekcije; klinični pregled; diagnostika